Sinc-Chebyshev Collocation Method for a Class of Fractional Diffusion-Wave Equations. (1st April 2014) - Mao, Zhi; Xiao, Aiguo; Yu, Zuguo; Shi, Long
Abstract : This paper is devoted to investigating the numerical solution for a class of fractional diffusion-wave equations with a variable coefficient where the fractional derivatives are described in the Caputo sense. The approach is based on the collocation technique where the shifted Chebyshev polynomials in time and the sinc functions in space are utilized, respectively. The problem is reduced to the solution of a system of linear algebraic equations. Through the numerical example, the procedure is tested and the efficiency of the proposed method is confirmed.